A nanofiber membrane and a preparation method and application thereof

By combining nano-lanthanum oxide functional particles with polyurethane through electrospinning and fiber bonding technology, a nanofiber membrane with high air permeability, waterproof and moisture-permeable properties and self-heating properties was prepared, which solved the multiple performance requirements of outdoor clothing fabrics in extreme environments and achieved excellent water-washing resistance.

CN120425507BActive Publication Date: 2026-02-06BOSIDENG DOWN WEAR LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510547873.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2026-02-06
Estimated Expiration
2045-04-28

AI Technical Summary

Technical Problem

Existing outdoor clothing fabrics are difficult to simultaneously provide waterproof, windproof, breathable, and warm functions in cold or humid environments, and their durability is insufficient. Traditional multi-layered fabrics have complex structures and increased weight, while existing patented waterproof and breathable membranes have poor water resistance.

Method used

Nanofiber membranes were prepared by combining nano-lanthanum oxide functional particles with polyurethane through electrospinning and fiber bonding technology. The addition of nano-lanthanum oxide heating functional particles formed a porous structure, which enhanced the stability of the fiber bonding points and the water-washing resistance.

Benefits of technology

The prepared nanofiber membrane has high air permeability, waterproof and moisture permeability and excellent water washability. The hydrostatic pressure reaches 6900-9800 mmH2O, the moisture permeability is 5300-8800 g/(m2·24h), the far-infrared temperature rise is 2.5-3.8℃, and the hydrostatic pressure drops by less than 8% after 10 washes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005381237800000091
    Figure BDA0005381237800000091
  • Figure BDA0005381237800000101
    Figure BDA0005381237800000101
Patent Text Reader

Abstract

The application relates to a nanofiber membrane and a preparation method and application thereof, and the preparation method comprises the following steps: (1) mixing polyurethane, nano lanthanum oxide, a waterproof agent and a solvent to obtain a spinning solution; (2) preparing an electrostatic spinning membrane through electrostatic spinning of the spinning solution; (3) spraying a finishing liquid on the electrostatic spinning membrane, and then performing heating treatment to obtain the nanofiber membrane. The polyurethane is stretched into superfine fibers through the electrostatic spinning technology, and a superhigh porous membrane similar to a spider web is prepared, the porous membrane has billions of nanoholes per square centimeter of the membrane, the nanofiber membrane has high air permeability and waterproof and moisture permeability, and the fibers are bound through a fiber bonding point technology, so that the fabric has excellent washing resistance. The nano lanthanum oxide heating functional particles are added to endow the nanofiber membrane with heating and heat storage functions, and further improve the washing resistance of the fabric.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of textiles, in particular to a nanofiber membrane and a preparation method and application thereof. BACKGROUND

[0002] With the increasing popularity of outdoor activities, people's performance requirements for outdoor clothing materials are constantly improving. The water resistance, high moisture permeability and warmth retention performance of the fabric have become the core demand of outdoor clothing fabric. In cold or humid environments, traditional fabrics often cannot simultaneously consider water resistance, wind resistance, air permeability and warmth retention, which limits their use in extreme environments.

[0003] In the prior art, the above functions are often achieved by stacking multiple layers of fabric, but this approach has problems such as insufficient air permeability, complex structure, and increased weight.

[0004] CN115595732A discloses a high-strength electrospun polyurethane waterproof and moisture-permeable membrane and a preparation method thereof. DMF and methyl acetate are mixed to obtain a spinning solution, and a waterproof agent is dispersed in the prepared solvent; TPU particles are dispersed into the solution until a transparent spinning solution is formed, and the spinning solution is electrospun. However, this patent still has the problem of poor durability. After washing, the structure of the membrane changes, resulting in a decrease in waterproof performance.

[0005] CN117468172A discloses a waterproof, high-moisture-permeable and air-permeable electrospun membrane, a preparation method and application thereof. Although the electrospun membrane prepared thereby has high moisture permeability and air permeability, its waterproofness and warmth retention performance still need to be improved.

[0006] Therefore, it has become a research hotspot in the field of outdoor clothing materials to develop a lightweight outdoor clothing fabric with waterproofness, high moisture permeability, wash resistance and heat retention and warmth retention performance. SUMMARY

[0007] To solve the above technical problems, the present application provides a nanofiber membrane and a preparation method and application thereof by innovative material combination and process optimization. By adding nano lanthanum oxide functional particles and using electrospinning technology and fiber bonding point technology, the hydrostatic pressure of the prepared nanofiber membrane can reach 6900-9800mmH2O, the moisture permeability can reach 5300-8800g / (m 2 ·24h), the far infrared temperature rise can reach 2.5-3.8℃, and the nanofiber membrane has excellent wash resistance. The further prepared clothing fabric can meet the multiple needs of consumers in complex environments, and promotes the progress of outdoor clothing technology.

[0008] To achieve this purpose, the present application adopts the following technical solutions:

[0009] In a first aspect, the present application provides a preparation method of a nanofiber membrane, comprising the following steps:

[0010] (1) mixing polyurethane, nano lanthanum oxide, a water repellent agent and a solvent to obtain a spinning solution;

[0011] (2) preparing an electrospun membrane by electrospinning the spinning solution;

[0012] (3) spraying a finishing liquid on the electrospun membrane, and then performing a heating treatment to obtain the nanofiber membrane.

[0013] In one aspect, the present application uses electrospinning and fiber bonding technology to stretch polyurethane into ultra-fine fibers, and then makes an ultra-high porous membrane similar to a spider web, with billions of nanoholes per square centimeter of the membrane, so that the membrane has high air permeability and water-repellent and moisture-permeable properties. In another aspect, the present application adds nano lanthanum oxide heat generating functional particles to endow the nanofiber membrane with excellent heat storage and warmth retention performance. The nano lanthanum oxide has a high specific surface area and a small size effect, so it can be better combined with the base material. The presence of nano particles can enhance the interaction force between fibers, thereby improving the strength and stability of the bonding points and the wash resistance of the fabric.

[0014] Preferably, the spinning solution includes, by weight, 3-5 parts (for example, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts, etc.) of nano lanthanum oxide, 12-20 parts (for example, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, etc.) of polyurethane, 1-4 parts (for example, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts, etc.) of a water repellent agent, and 71-84 parts (for example, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts or 84 parts, etc.) of a solvent.

[0015] Preferably, the particle size of the nano lanthanum oxide is 100-300 nm, for example, 100 nm, 150 nm, 200 nm, 250 nm or 300 nm, etc.

[0016] Preferably, the number average molecular weight of the polyurethane is 50,000-70,000, for example, 50,000, 55,000, 60,000, 65,000 or 70,000, etc.

[0017] Preferably, the water repellent agent includes a fluorine-free water repellent agent, and further preferably a hydroxymethyl type water repellent agent.

[0018] Preferably, the solvent includes N,N dimethylacetamide, tetrahydrofuran and water.

[0019] Preferably, the temperature of the mixing in step (1) is 55-65℃, for example, it can be 55℃, 57℃, 59℃, 60℃, 62℃, 64℃ or 65℃, etc.

[0020] Preferably, the mixing in step (1) further comprises a defoaming treatment step.

[0021] Preferably, the time of the defoaming treatment is 12-36h, for example, it can be 12h, 18h, 24h, 30h or 36h, etc.

[0022] Preferably, the electrospinning in step (2) is carried out in an electrospinning machine.

[0023] Preferably, the operating voltage of the electrospinning is 10-25kv, for example, it can be 10kv, 13kv, 15kv, 18kv, 20kv, 23kv or 25kv, etc.

[0024] Preferably, the receiving distance of the electrospinning is 12-16cm, for example, it can be 12cm, 13cm, 14cm, 15cm or 16cm, etc.

[0025] Preferably, the spinning flow of the electrospinning is 0.05-0.08mm / min, for example, it can be 0.05mm / min, 0.06mm / min, 0.07mm / min or 0.08mm / min, etc.

[0026] Preferably, the operating temperature of the electrospinning is 40-60℃, for example, it can be 40℃, 45℃, 50℃, 55℃ or 60℃.

[0027] Preferably, the operating humidity of the electrospinning is 25-75%, for example, it can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or 75%, etc.

[0028] Preferably, the step (2) further comprises a drying step.

[0029] Preferably, the temperature of the drying step is 75-85℃, for example, it can be 75℃, 77℃, 80℃, 82℃ or 85℃, etc.

[0030] Preferably, the finishing liquid in step (3) is a mixed solution of N,N dimethylacetamide and tetrahydrofuran diluted with water.

[0031] Preferably, the mass ratio of N,N dimethylacetamide and tetrahydrofuran in the finishing liquid is 1:(0.5-2), for example, it can be 1:0.5, 1:1, 1:1.5 or 1:2, etc.

[0032] Preferably, the volume concentration of N,N dimethylacetamide in the finishing liquid is 0.1-1%, for example, it can be 0.1%, 0.2%, 0.4%, 0.6%, 0.8% or 1%, etc.

[0033] Preferably, the heating treatment in step (3) is at a temperature of 180-200°C (for example, it can be 180°C, 185°C, 190°C, 195°C or 200°C, etc.) for 1-2 min (for example, it can be 1 min, 1.2 min, 1.4 min, 1.5 min, 1.6 min, 1.8 min or 2 min, etc.).

[0034] Preferably, step (3) is specifically: placing the prepared electrospun membrane in a sealed box, spraying the finishing liquid in the sealed box using a sprayer, heating the sealed box to 180-200°C (for example, it can be 180°C, 185°C, 190°C, 195°C or 200°C, etc.) after standing for 30-60 s (for example, it can be 30 s, 40 s, 50 s or 60 s, etc.), and taking out and cooling after heating for 1-2 min (for example, it can be 1 min, 1.2 min, 1.4 min, 1.5 min, 1.6 min, 1.8 min or 2 min, etc.), to obtain the nanofiber membrane.

[0035] The present application sprays the finishing liquid on the surface of the electrospun membrane through the bonding point technology, dissolves part of the fibers in the electrospun membrane through the spray sprayed by the sprayer, accelerates the flowability of the molecules on the surface of the fibers, and realizes the recrystallization of the nanofibers at the cross point position through the heating treatment to make the solvent volatilize, thereby preparing the nanofiber membrane with a multi-layer network structure in micro-morphology, and the addition of the nanometer lanthanum oxide further provides the crystallization sites for the recrystallization and promotes the formation of the fiber bonding and the fiber membrane.

[0036] In the second aspect, the present application provides a nanofiber membrane prepared by the preparation method of the first aspect.

[0037] In the third aspect, the present application provides a garment fabric composed of the nanofiber membrane of the second aspect and a base cloth.

[0038] Compared with the prior art, the present application has at least the following beneficial effects:

[0039] (1) The nanofiber membrane prepared by the present application has excellent waterproof and moisture permeable properties and washing resistance by using the electrospinning and fiber bonding technologies.

[0040] (2) The present application makes the nanofiber membrane have the heat storage function by adding the nano lanthanum oxide heat generating functional particles, and the nano lanthanum oxide has a high specific surface area and a small size effect, so that it can be better combined with the base material, thereby improving the wash resistance of the fabric.

[0041] (2) Specifically, the hydrostatic pressure of the nanofiber membrane prepared by the present application can reach 6900-9800mmH2O, the moisture permeability can reach 5300-8800g / (m 2 ·24h), and the far infrared temperature rise can reach 2.5-3.8℃; after washing for 10 times, the hydrostatic pressure decreases by less than 8%, and the wash resistance is excellent. DETAILED DESCRIPTION

[0042] In order to facilitate the understanding of the present application, the present application lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present application, and should not be regarded as a specific limitation on the present application.

[0043] In the following specific embodiments of the present application, the specific information of the materials used is as follows:

[0044] 1. Polyurethane: purchased from Shanghai Housen Polyurethane Co., Ltd., number average molecular weight is 50000-70000;

[0045] 2. Nano lanthanum oxide: purchased from Jinlei Technology;

[0046] 3. Water repellent, fluorine-free water repellent hydroxymethyl stearic acid amide FI05, purchased from Guangzhou Chuangju Chemical Technology Co., Ltd.

[0047] Example 1

[0048] A preparation method of a nanofiber membrane, the preparation method comprising the following steps:

[0049] (1) Polyurethane (16 parts), nano lanthanum oxide (4 parts), water repellent FI05 (2 parts), N,N dimethylacetamide (15 parts), tetrahydrofuran (16 parts) and water (47 parts) are stirred and mixed at 60℃ until the raw materials are completely dissolved, and the mixed solution is left to stand for 24h for degassing treatment, to obtain a spinning solution;

[0050] (2) The spinning solution is assembled in a 10mL syringe and fixed on an electrospinning device, and an electrospinning film is obtained by electrospinning. The electrospinning film is then placed in a 80℃ drying oven for drying to remove the residual solvent on the surface of the film. The voltage of the electrospinning device is 18kv, the receiving distance is 14cm, the spinning flow is 0.06mm / min, the temperature is 50℃, and the humidity is 50%.

[0051] (3) mixing N,N dimethylacetamide and tetrahydrofuran at 1:0.5, diluting the mixture with water to a concentration of 0.2% of N,N dimethylacetamide to obtain a finishing liquid, placing the electrospun film in a sealed box, spraying the finishing liquid in the sealed box using a sprayer, heating the sealed box to 200°C after standing for 50s, heating for 1 min to volatilize the solvent, and then quickly taking out and cooling to obtain the nanofiber membrane.

[0052] Example 2

[0053] A method of preparing a nanofiber membrane, the method comprising the steps of:

[0054] (1) mixing polyurethane (12 parts), nano lanthanum oxide (3 parts), water repellent FI05 (1 part), N,N dimethylacetamide (10 parts), tetrahydrofuran (12 parts), and water (62 parts) at 55°C to mix and stir until the raw materials are completely dissolved, and then standing the mixed solution for 18h to perform a degassing treatment to obtain a spinning solution;

[0055] (2) loading the spinning solution in a 10 mL syringe and fixing it on an electrospinning device to obtain an electrospun film by electrospinning, and then drying the electrospun film in a 75°C drying box to remove residual solvents on the surface of the film, wherein the voltage of the electrospinning device is 10kv, the receiving distance is 12cm, the spinning flow is 0.05mm / min, the temperature is 40°C, and the humidity is 25%.

[0056] (3) mixing N,N dimethylacetamide and tetrahydrofuran at 1:0.5, diluting the mixture with water to a concentration of 0.2% of N,N dimethylacetamide to obtain a finishing liquid, placing the electrospun film in a sealed box, spraying the finishing liquid in the sealed box using a sprayer, heating the sealed box to 200°C after standing for 50s, heating for 1 min to volatilize the solvent, and then quickly taking out and cooling to obtain the nanofiber membrane.

[0057] Example 3

[0058] A method of preparing a nanofiber membrane, the method comprising the steps of:

[0059] (1) mixing polyurethane (20 parts), nano lanthanum oxide (5 parts), water repellent FI05 (4 parts), N,N dimethylacetamide (20 parts), tetrahydrofuran (20 parts), and water (31 parts) at 65°C to mix and stir until the raw materials are completely dissolved, and then standing the mixed solution for 24h to perform a degassing treatment to obtain a spinning solution;

[0060] (2) The spinning solution is assembled in a 10 mL syringe and fixed on the electrospinning device, and an electrospinning film is obtained by electrospinning. The electrospinning film is placed in a drying oven at 85°C to remove the residual solvent on the surface of the film. The voltage of the electrospinning device is 25kv, the receiving distance is 16cm, the spinning flow is 0.08mm / min, the temperature is 60°C, and the humidity is 75%.

[0061] (3) N,N dimethylacetamide is mixed with tetrahydrofuran at a ratio of 1:2, and the mixture is diluted with water to a concentration of 0.8% N,N dimethylacetamide. After that, a finishing solution is obtained. The electrospinning film is placed in a sealed box, and the finishing solution is sprayed into the sealed box using a sprayer. After standing for 60s, the sealed box is heated to 190°C, and the solvent is volatilized after heating for 2min. The nanofiber film is obtained by quickly taking it out and cooling it.

[0062] Example 4

[0063] A method for preparing a nanofiber film, which is different from example 1 in that the amount of nanometer lanthanum oxide added to the spinning solution is 1 part.

[0064] Example 5

[0065] A method for preparing a nanofiber film, which is different from example 1 in that the amount of nanometer lanthanum oxide added to the spinning solution is 8 parts.

[0066] Example 6

[0067] A method for preparing a nanofiber film, which is different from example 1 in that the volume concentration of N,N dimethylacetamide in the finishing solution is 2%.

[0068] Example 7

[0069] A method for preparing a nanofiber film, which is different from example 1 in that the particle size of nanometer lanthanum oxide in the spinning solution is 50nm.

[0070] Example 8

[0071] A method for preparing a nanofiber film, which is different from example 1 in that the particle size of nanometer lanthanum oxide in the spinning solution is 500nm.

[0072] Comparative Example 1

[0073] A method for preparing a nanofiber film, which is different from example 1 in that the spinning solution does not contain nanometer lanthanum oxide.

[0074] Comparative Example 2

[0075] A method for preparing a nanofiber film, which is different from example 1 in that the spinning solution does not contain a water repellent.

[0076] Comparative Example 3

[0077] A preparation method of an electrospun membrane, comprising the following steps:

[0078] (1) Stir and mix polyurethane (16 parts), nano lanthanum oxide (4 parts), water repellent agent F105 (2 parts), N,N dimethylacetamide (15 parts), tetrahydrofuran (16 parts) and water (47 parts) at 60°C until all raw materials are dissolved, and then obtain a spinning solution after the mixed solution is left standing for 24 h for defoaming treatment;

[0079] (2) Assemble the spinning solution in a 10 mL syringe and fix it on an electrospinning device, and obtain an electrospun membrane by electrospinning. Then, place the electrospun membrane in a drying oven at 80°C to remove residual solvents on the surface of the membrane. The voltage of the electrospinning device is 18 kv, the receiving distance is 14 cm, the spinning flow is 0.06 mm / min, the temperature is 50°C, and the humidity is 50%.

[0080] Test method

[0081] (1) Hydrostatic pressure (hydrostatic pressure (mmH2O)): tested according to GB / T 4744-2013;

[0082] (2) Moisture permeability g / (m 2 ·24h): tested according to GB / T 12704.2-2009 Evaporation method, test conditions: temperature 38°C, humidity 50%;

[0083] (3) Far infrared temperature rise (℃): tested according to GB / T Far Infrared Temperature Rise 30127.

[0084] Test results

[0085] The nano-fiber membranes prepared in Examples 1-6 and Comparative Examples 1-3 were tested for performance, and the results are shown in Table 1.

[0086] Table 1

[0087]

[0088]

[0089] From the test results, it can be seen that:

[0090] (1) From Examples 1 to 8, it can be seen that the hydrostatic pressure of the nano-fiber membrane prepared by the present application can reach 6900-9800 mmH2O, and the moisture permeability can reach 5300-8800 g / (m 2·24h), the far infrared temperature rise can reach 2.5-3.8℃, and the nanofiber membrane has excellent waterproof and moisture permeability and self-heating performance; the hydrostatic pressure decreases by less than 8% after washing 10 times, and the nanofiber membrane has excellent washing resistance.

[0091] (2) As can be seen from Example 1 and Examples 4-5, too little addition of nano lanthanum oxide leads to poor self-heating function of the nanofiber membrane, and too much addition of nano lanthanum oxide affects the water and moisture resistance of the nanofiber membrane.

[0092] (3) As can be seen from Example 1 and Example 6, when the concentration of the organic solvent in the finishing liquid is high, the organic solvent has a serious effect on the dissolution of the electrospun membrane, and affects the moisture permeability of the nanofiber membrane.

[0093] (4) As can be seen from the examples and Examples 7-8, when nano lanthanum oxide functional particles with small particle size are added, the infrared radiation of the heating particles is shifted, the far infrared temperature rise effect is poor, and the heating and heat preservation function of the nanofiber membrane is poor; when nano lanthanum oxide functional particles with large particle size are added, the washing fastness of the nanofiber membrane is poor, and the water pressure resistance of the nanofiber membrane is decreased.

[0094] (5) As can be seen from Example 1 and Comparative Examples 1-2, the nanofiber membrane has excellent heating and heat storage functions and water and moisture resistance by adding the waterproof agent and the nano lanthanum oxide functional particles in cooperation.

[0095] (6) As can be seen from Example 1 and Comparative Example 3, the washing resistance of the fabric is improved by the fiber bonding point technology.

[0096] The applicant declares that the above description is only a specific embodiment of the present application, but the protection scope of the present application is not limited thereto. It should be understood by those skilled in the art that any changes or replacements within the technical scope disclosed by the present application can be easily thought of by those skilled in the art, and all fall within the protection scope and disclosure scope of the present application.

Claims

1. A method for preparing a nanofiber membrane, characterized in that, The preparation method includes the following steps: (1) Polyurethane, nano-lanthanum oxide, waterproofing agent and solvent are mixed to obtain spinning solution; (2) Electrospun membrane is prepared by electrospinning the spinning solution; (3) The finishing liquid is sprayed onto the electrospun membrane and then heated to obtain the nanofiber membrane; The spinning solution comprises, by weight, 3-5 parts of nano-lanthanum oxide, 12-20 parts of polyurethane, 1-4 parts of waterproofing agent, and 71-84 parts of solvent.

2. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The lanthanum oxide nanoparticles have a particle size of 100-300 nm.

3. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The polyurethane has a number-average molecular weight of 50,000-70,000.

4. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The waterproofing agent includes a fluorine-free waterproofing agent.

5. The method for preparing the nanofiber membrane according to claim 4, characterized in that, The waterproofing agent is a hydroxymethyl waterproofing agent.

6. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The solvent includes any one or a combination of at least two of N,N-dimethylacetamide, tetrahydrofuran, and water.

7. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The mixing temperature in step (1) is 55-65℃.

8. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The mixing process described in step (1) also includes a degassing process.

9. The method for preparing the nanofiber membrane according to claim 8, characterized in that, The degassing treatment time is 12-36 h.

10. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The electrospinning in step (2) is carried out in an electrospinning machine.

11. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The operating voltage for electrospinning in step (2) is 10-25 kV.

12. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The receiving distance for electrospinning in step (2) is 12-16 cm.

13. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The electrospinning flow rate in step (2) is 0.05-0.08 mm / min.

14. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The electrospinning operation temperature in step (2) is 40-60℃.

15. The method for preparing a nanofiber membrane according to claim 1, characterized in that, The operating humidity for electrospinning in step (2) is 25-75%.

16. The method for preparing a nanofiber membrane according to claim 1, characterized in that, The step (2) is followed by a drying step.

17. The method for preparing a nanofiber membrane according to claim 16, characterized in that, The drying step is performed at a temperature of 75-85°C.

18. The method for preparing a nanofiber membrane according to claim 1, characterized in that, The finishing solution mentioned in step (3) is a mixed solution of N,N-dimethylacetamide and tetrahydrofuran diluted with water.

19. The method for preparing a nanofiber membrane according to claim 18, characterized in that, The mass ratio of N,N-dimethylacetamide to tetrahydrofuran in the finishing solution is 1:(0.5-2).

20. The method for preparing a nanofiber membrane according to claim 18, characterized in that, The volume concentration of N,N-dimethylacetamide in the finishing solution is 0.1-1%.

21. The method for preparing the nanofiber membrane according to claim 1, characterized in that, The heating temperature in step (3) is 180-200℃, and the heating time is 1-2 min.

22. The method for preparing the nanofiber membrane according to claim 1, characterized in that, Step (3) is as follows: Place the prepared electrospun membrane in a sealed box, spray the finishing liquid into the sealed box using a sprayer, let it stand for 30-60 seconds, then heat the sealed box to 180-200℃, heat for 1-2 minutes, and then take it out and cool it to obtain the nanofiber membrane.

23. A nanofiber membrane prepared by the preparation method according to any one of claims 1-22.

24. A clothing fabric, characterized in that, The garment fabric is composed of the nanofiber membrane described in claim 23 and a base fabric.

Citation Information

Patent Citations

  • Rare-earth metal oxide / polyacrylonitrile (PAN) composite fiber and preparation method thereof

    CN104032403A

  • Waterproof electrostatic spinning membrane with high moisture permeability and air permeability as well as preparation method and application thereof

    CN117468172A